A novel rapid alloy development method towards powder bed additive manufacturing, demonstrated for binary Al-Ti, -Zr and -Nb alloys - Leijon, Freddy; Wachter, Sebastian; Fu, Zongwen; Körner, Carolin; Skjervold, Svein; Moverare, Johan (Materials & Design, 2021)
Powder bed fusion (PBF) methods offer the best material properties among metal additive manufacturing (AM) processes. Yet, alloy development for PBF is only at its infancy and has a great untapped potential. This originates from the high solidification rate within the melt pool and to exploit the full potential of materials produced by PBF methods, a diligent work lies ahead. This paper presents a high-throughput method to rapidly screen large compositional alloy intervals experimentally for their PBF feasibility, which can drastically reduce the time needed for alloy development and provide valuable data for modelling. Our method consists of two steps; co-sputtering and electron beam re-melting. First step produces an alloy gradient film on a sheet substrate. The film is then re-molted to produce a PBF mimicked microstructure. The method is successfully demonstrated on binary systems; Al-Ti,-Zr and-Nb and produced gradients in compositional ranges of 3-50 wt%Ti, 1-15 wt%Zr and 2-15 wt%Nb over a length of 200 mm. From the produced materials, the alloying efficiency could be investigated and determined regarding hardness and grain refinement. Zr shows the highest strength contribution per at% and the best grain refinement at low levels. However, at higher levels grain refinement efficiency decreases for Zr. (c) 2021 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY license (http:// creativecommons.org/licenses/by/4.0/).
CRIS-Team WoS Importer:2021-10-29

Development of a Material Extrusion Additive Manufacturing Process of 1.2083 steel comprising FFF Printing, Solvent and Thermal Debinding and Sintering - Vetter, Johannes; Huber, Florian; Wachter, Sebastian; Körner, Carolin; Schmidt, Michael (Procedia CIRP, 2022)
In recent years, Fused Filament Fabrication (FFF) of feedstock comprising metal powder and a polymer binder system attracted more and more attention as an extrusion-based Additive Manufacturing method. Allowing for the production of intricate geometries at reasonably low cost, FFF and subsequent debinding and sintering is an attractive solution for producing complex parts made of metals or ceramics. This study investigates the FFF, debinding and sintering process chain for 1.2083 (AISI 420) tool steel. The effect of printing temperature, printing speed and filament feed rate on the density of the green body was evaluated. With regard to the subsequent solvent debinding the required time for complete binder removal was determined as a function of the maximum part thickness. Based on a thermogravimetric analysis (TGA) the decomposition behavior of the remaining insoluble binder was monitored and accordingly a temperature program for the thermal debinding was derived. The sintering curve was determined by dilatometry. Finally, the capability of the process is demonstrated by manufacturing an impeller geometry and examining the resulting microstructure and hardness of the material.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Additive Manufacturing; FFF; Material Extrusion; Process Development; Sintering; Solven; Thermal Debinding; Tool Steel

Practically applicable water oxidation electrodes from 3D-printed Ti6Al4V scaffolds with surface nanostructuration and iridium catalyst coating - Hofer, André; Wachter, Sebastian; Döhler, Dirk; Laube, Armin; Sánchez Batalla, Beatriz; Fu, Zongwen; Weidlich, Claudia; Struckmann, Thorsten; Körner, Carolin; Bachmann, Julien (Electrochimica Acta, 2022)
This study establishes the applicability of 3D printing (additive manufacturing) towards the generation of titanium alloy scaffolds for water oxidation electrodes. The scaffolds can be subsequently nanostructured by electrochemical anodization to enhance their surface area and coated with iridium as the electrocatalyst. We focus on the characterization of the functional electrodes in process-relevant conditions (1 M HSO, 60 C, stirring) in terms of their performance and stability in a holistic manner. Various preparative conditions yield various patterns of performance and stability, as quantified by overpotentials in steady-state electrolyses, maximum current densities in dynamic voltammetry, surface roughness rf, and by overpotential increase, iridium loss, and decrease after 100 h of operation, on the other hand. In other words, the system is highly flexible and can be adapted to specific constraints depending on the application chosen.<br
Keywords: ALD; Electrochemistry; Heterogeneous catalysis; Iridium; Water splitting

Processing windows for Ti-6Al-4V fabricated by selective electron beam melting with improved beam focus and different scan line spacings - Pobel, Christoph; Osmanlic, Fuad; Lodes, Matthias; Wachter, Sebastian; Körner, Carolin (Rapid Prototyping Journal, 2019)
Purpose: Selective electron beam melting (SEBM) is a highly versatile powder bed fusion additive manufacturing method. SEBM is characterized by high energy densities which can be applied with nearly inertia free beam deflection at high speeds (<8.000 m/s). This paper aims to determine processing maps for Ti-6Al-4V on an Arcam Q10 machine with LaB6 cathode design. Design/methodology/approach: Scan line spacings of 100, 50 and 20 µm in a broad parameter range, focusing on high deflection and build speeds are investigated. Findings: There are broad processing windows for dense parts without surface flaws for all scan line spacings which are defined by the total energy input and the area melting velocity. Originality/value: The differences and limitations are discussed taking into account the beam properties at high beam energy and velocity as well as evaporation related loss of alloying components.
CRIS-Team Scopus Importer:2021-04-20
Keywords: CAD; Metals; Rapid prototyping; Research; Selective electron beam melting; Titanium